ARCHAEOLOGICAL DISCOVERIES ON MONTE ALBAN MEX - CASO (My University, 1943)
EXCAVATION of the Mixteco-Zapotecan necropolis on Monte Alban, near Oaxaca, MEX, which has been in progress under the direction of Dr. Alfonso Caso without interruption since 1932, has produced a remarkable assemblage of objects, ornamental and ceremon
NATURE
Keywords: ARCHAEOLOGICAL DISCOVERIES, MONTE ALBAN MEX; MULTIDISCIPLINARIA; CIENCIAS AUXILIARES DE LA HISTORIA; ARQUEOLOGIA